Increasing Motorcyclist Awareness (Night Riding) From Self-Reported Study on Rural Roads in Sabak Bernam with Three Proactive Measures - Sayuti, Badrul Amin; Ab.Ghani, Ahmad Raqib (Recent Trends in Civil Engineering and Built Environment, 2024)
Accidents in Sabak Bernam seems to be critical due to lack of awareness among motorcyclist especially at night time riding. Therefore, three safety proactive measure is aimed to increase the awareness among road user during night time especially for motorcycle users. By study this measured, the rider also can more aware so that can reduce the number of an accident. This three measure was studied due to the problems faced by many motorcyclist riding at night time especially at rural road in Sabak Bernam. The project were studied by using three main proactive measurement such as rear brake light, street lamp and road distress. The methodology of the study consists of a literature review to establish the study's objectives, data collecting using questionnaires, data analysis, and ultimately results and suggestions. The questionnaire were contain questions using the Likert scale. Data analysis techniques such as descriptive statistics and reliability analysis were used to analyse the data. The intended outcome of this study is that motorcycle riders' awareness will rise, resulting in a reduction in accidents.